DNA Methylation and Hydroxymethylation in Primary Colon Cancer and Synchronous Hepatic Metastasis - Udali, Silvia; De Santis, Domenica; Ruzzenente, Andrea; Moruzzi, Sara; Mazzi, Filippo; Beschin, Greta; Tammen, Stephanie A.; Campagnaro, Tommaso; Pattini, Patrizia; Olivieri, Oliviero; Guglielmi, Alfredo; Choi, Sang-Woon; et al. (Frontiers in Genetics, 2018)
Colon cancer is one of the most frequent solid tumor and simultaneous diagnosis of primary colon cancer and liver metastases occurs in about one fourth of cases. The current knowledge on epigenetic signatures, especially those related to hydroxymethylation in primary cancer tissue, synchronous metastasis and blood circulating cells is lacking. This study aimed to investigate both methylcytosine (mCyt) and hydroxymethylcytosine (hmCyt) status in the DNA of individual patients from colon cancer tissue, synchronous liver metastases, and in cancer-free colon and liver tissues and leukocytes. Patients undergoing curative surgery (n=16) were enrolled and their laboratory and clinical history data collected. The contents of mCyt and hmCyt were determined by a liquid chromatography/mass spectrometry (LC/MS/MS) method in DNA extracted from primary colon cancer, synchronous hepatic metastatic tissues and homologous cancer-free tissues, i.e., colon and liver tissues as well as leukocytes. The mCyt and hmCyt levels were compared between cancerous and cancer-free tissues, and correlations between leukocytes and colon/liver tissues for both the mCyt and hmCyt levels were evaluated. The mCyt levels were similar in primary colon cancer and liver metastasis tissues (4.69%±0.37 vs 4.77%±0.38, respectively, p=0.535), and both primary and metastatic tissues were hypomethylated compared to cancer-free colon (4.98%±0.26). The difference in the mCyt content between cancerous and cancer-free colon tissues was significantly lower in primary colon cancer (p=0.004), but not in liver metastasis (p=0.148). The hmCyt content was similar in primary colon cancer compared to liver metastasis (0.035%, C.I. 0.024-0.052% versus 0.035%, C.I. 0.021-0.058%, respectively, p=0.905) and markedly depleted compared to the cancer-free colon (0.081%, C.I. 0.055-0.119%) with a statistically significant difference (p<0.05) for both comparisons. The mCyt levels showed a borderline correlation between leukocytes and colon cancer tissue (Pearson’s correlation coefficient=0.51, p=0.052) while no correlations were detected for the hmCyt levels. In conclusion, primary colon cancer and synchronous liver metastasis tissues showed a similar epigenetic status but were significantly hypomethylated and hypohydroxymethylated as compared to homologous cancer-free colon tissues.